A duty of candour: A change in approach. (January 2014) - Mellor, Christopher
This article (written in April 2013) considers the observations and recommendations made in the Report of the Mid Staffordshire NHS Foundation Trust Public Inquiry as to a duty of candour and, in particular, the recommendation that there should be a statutory duty of candour imposed on healthcare providers, as well as on registered medical practitioners, nurses and other registered professionals, who believe or suspect that patient treatment or care has caused death or serious injury. The article details the Government's initial response to such recommendations, in which it indicated an intention to introduce a statutory duty for health and care providers, and sets out the contractual duty of candour that is currently included in the NHS Standard Contract for 2013/14 (SC35). There is then an analysis of the terms of the contractual duty contrasted with those of the proposed statutory duty; a look at the limitations of the contractual duty; a discussion of some of the issues that may arise in relation to when the relevant duty (either contractual or statutory) will be triggered; a consideration of the apparent novelty of a statutory duty of candour in English law; and a brief discussion in relation to the potential remedies, penalties and offences that may be adopted if such a statutory duty comes into force. In conclusion, on any basis the imposition of the contractual duty of candour and the intention to introduce some form of statutory duty heralds a new era in relation to candour in healthcare.